(3efgd GdChdjGA heTQH GdCUajGA ef SdGdI GdehUd GdMOHGA (B((3Ch(B) (3aj SGOGJ GdehUd GdMOHGAs - (3eMeO Cejf Hf NjQ Gddg Hf eMehO Hf ehSi GdNWjH, GdYeQj,J (B1203 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CQTO ChdjGAg Edi ebGe GdYdhe s
(3ai JGQjN GdehUd hJQGLe ef cGf ajgG ef GdYdeGA hGdhdGI hGdChdjGAs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B294s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B374 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B269 s
Keywords: (3GdJGQjNs